2012
DOI: 10.2522/ptj.20110282
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Therapist-Based Versus Robot-Assisted Bilateral Arm Training on Motor Control, Functional Performance, and Quality of Life After Chronic Stroke: A Clinical Trial

Abstract: Compared with CT, TBAT and RBAT exhibited differential effects on outcome measures. Therapist-based BAT may improve temporal efficiency, smoothness, trunk control, and motor impairment of the distal upper limb. Robot-assisted BAT may improve shoulder flexion and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 50 publications
1
53
0
2
Order By: Relevance
“…The same research group carried out an RCT with patients with chronic stroke, comparing Bi-Manu-Track bilateral upper limb training with therapist-based bilateral upper limb training and a control treatment [46]. All groups received treatment for 90–105 minutes per session, 5 sessions per week, for 4 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…The same research group carried out an RCT with patients with chronic stroke, comparing Bi-Manu-Track bilateral upper limb training with therapist-based bilateral upper limb training and a control treatment [46]. All groups received treatment for 90–105 minutes per session, 5 sessions per week, for 4 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…29-41 The meta-analysis in a 2012 Cochrane review demonstrated that robot-assisted arm training improved upper limb function (standardized mean difference 0.45; 95% confidence interval (CI), 0.20 to 0.69; P =0.0004) 42. However, more detailed analysis is needed to develop guidelines for individual stroke rehabilitation.…”
Section: Robot-assisted Therapy For Upper Limb and Hand Motor Functionmentioning
confidence: 99%
“…Nine of the 14 randomized controlled trials that examined robot-assisted therapy with end-effector-type devices assessed the influence of robot-assisted training on activities of daily living (ADL) in patients with stroke 29,30,32-35,38-41. These nine reports demonstrated that robot-assisted training yielded similar or better effects on ADL in comparison with conventional therapy.…”
Section: Robot-assisted Therapy For Upper Limb and Hand Motor Functionmentioning
confidence: 99%
“…9 Motor replacement system controlled through an invasive BMI system. Source BBC demonstrated [95][96]. The main drawback is that these robotic systems can lead patients to passively perform their rehabilitation movements since the device executes sufficient force to impose the required movements and they are not sensitive to the effort exerted by the patients [97][98].…”
Section: Rehabilitation Robotic Systemsmentioning
confidence: 99%
“…These therapeutic applications include motor relearning for upper and lower limb and shoulder pain reduction after stroke. There is growing evidence that muscle electrostimulation, especially those approaches that incorporate specific task strategies, is effective in this motor learning [95].…”
Section: Rehabilitation Robotic Systemsmentioning
confidence: 99%